Growth, biochemical, and antioxidant response of pot marigold (Calendula officinalis L.) grown in fly ash amended soil. Issue 1 (2nd January 2023) - Varshney, Ayushi; Dahiya, Praveen; Mohan, Sumedha
Abstract: The present study was carried out to determine the impact of FA application on growth performance, biochemical parameters, and antioxidant defense activity of Calendula officinalis . The results revealed that under a low dose of FA (40%) amended soil, the plant growth performance and metal tolerance index (MTI) were increased compared to control plants and further decreased with increased FA application (60%, 80%, and 100% FA). In addition, the incorporation of 40% FA in soil not only improved the physicochemical properties of soil but also increased the biochemical parameters in the Calendula plant, however, these parameters declined under high FA applications. It was also observed that antioxidant enzyme activity (SOD, CAT, POD, and APX) in leaves of Calendula officinalis increased at high FA application (100% FA) to combat heavy metal stress from FA. The overall study suggests that 40% FA amended soil is the best suitable dose for growing Calendula officinalis and can be considered as metal tolerant species for phytoremediation of 40% FA amended soil. Novelty statement: Fly ash (FA) management is a major problem nowadays. The present study was carried out for FA utilization and to determine the impact of FA amended soil on growth performance, antioxidant properties, and biochemical attributes of Calendula officinalis . This is a sustainable approach in which waste (FA) utilization was done simultaneously with the enhancement in response of the medicinally potent Calendula species. The novelty of this study also suggests that Calendula has phytoremediation potential for remediation of heavy metal polluted soil. Further, the relationship between the growth, biochemical parameters, and antioxidant defense mechanism of Calendula grown on FA amended soil was studied which has not been studied so far. It was found that Calendula is a hyperaccumulator that can adapt to heavy metal stress from FA due to its ability to mitigate oxidative damage. Statistical analysis (ANOVA, Duncan's multiple range test, and PCA) was done for the results obtained using SPSS (11.5) and Origin 8 Pro software. Graphical Abstract: UF0001